Conflicting Interests and the Effect of Fiduciary Duty: Evidence from Variable Annuities - Egan, Mark; Ge, Shan; Tang, Johnny (Review of Financial Studies, 2022)
We examine the variable annuity market to study conflicts of interest and the effect of fiduciary duty in brokerage markets. Insurers typically pay brokers higher commissions for selling more expensive annuities. Our results indicate that sales are four times as sensitive to brokers’ interests as to investors’. To limit conflicts of interest, the Department of Labor proposed a rule in 2016 holding brokers to a fiduciary standard. We find that after the proposal, sales of high-expense products fell by 52% as sales became more sensitive to expenses. Based on our structural estimates, investor welfare improved overall. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.